2021
DOI: 10.1111/nuf.12636
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between workplace deviant behaviors and organizational justice among nurses: A cross‐sectional survey

Abstract: Aim This study aimed to determine the correlations between workplace deviant behaviors (WDBs) and the levels of the perceived organizational justice among Iranian nurses. Design This was a cross‐sectional quantitative research. Methods The present research was conducted on 424 nurses selected by a convenience sampling method in 2019 (May–August) in Tabriz, Iran. A self‐administered questionnaire, including demographic information, organizational justice, and WDBs, was used for data collection. The data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
4
8
0
Order By: Relevance
“…The results of the current research show a negative relationship between organizational justice and workplace deviance. These findings are also in line with the prior literature, which shows a negative relationship between these two variables (Berry et al , 2007; Colquitt et al , 2006; Faheem and Mahmud, 2015), specifically in the context of hospital nursing staff (Hashish, 2020; Kakemam et al , 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the current research show a negative relationship between organizational justice and workplace deviance. These findings are also in line with the prior literature, which shows a negative relationship between these two variables (Berry et al , 2007; Colquitt et al , 2006; Faheem and Mahmud, 2015), specifically in the context of hospital nursing staff (Hashish, 2020; Kakemam et al , 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Nurses play an important role in health-care organizations as they provide health-care services and are connected with human life; thus, a minor mistake, neglect or any negative behavior at work can bring irreparable injuries to patients (Kakemam et al , 2021). Thus, there is growing interest among scholars and practitioners regarding the negative workplace behaviors in the health-care sector, specifically related to the nursing staff.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Japanese study showed that female managers and professionals who suffer from low interpersonal justice in a workplace with unsupportive supervisors are more likely to engage in unhealthy coping behaviors to manage their stress [ 38 ]. Low perceived organizational justice is often associated with deviant behaviors [ 39 , 40 ]. Healthcare workers’ perceptions of organizational justice significantly predict turnover intention [ 41 , 42 ] and job satisfaction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kabiri et al (2022) found that 21% of their Iranian respondents engaged in occupational deviance behavior. Other studies have also uncovered the significant prevalence of occupational deviance across Iranian organizations (e.g., Bekhradinasab & Zholanezhad, 2021;Ghaedamini Harouni et al, 2022;Kakemam et al, 2021;Pooladi Kharasha & Esmaeili Shad, 2019;Teimouri et al, 2021). Lastly, there have been previous attempts to examine the issue of workplace deviance in the Iranian banking industry (Baghini et al, 2014;Ebrahimpour Ahandani et al, 2019), but most of these studies have been conducted from a management perspective.…”
Section: Introductionmentioning
confidence: 98%